Eternal sunshine of the spotless mind [videorecording (DVD)] - Gondry, Michel; Carrey, Jim, 1962-; Winslet, Kate; Dunst, Kirsten, 1982-; Ruffalo, Mark; Wood, Elijah, 1981- (Universal, 2004)
When Joel discovers that his girlfriend, Clementine, has had their tumultuous relationship erased from her mind through an experimental scientific procedure, he decides to ease his own pain by getting the same treatment. But, as each memory of Clementine is systematically eliminated, Joel suddenly realizes how much he still loves her and desperately attempts to reverse the process.